The Concept of Tawakkal in the Qur'an and Hadith and its Implications for Modern Islamic Business Practices - Jalal Ikram, Abdi Dzul; Abubakar, Achmad; Irham, Muhammad; Said, Wardana (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study examines the concept of tawakkal in the Qur'an and Hadith and its implications for contemporary sharia business practices. Tawakkal is understood as a combination of maximum effort and submission of results to Allah. Using the library research method, this study analyzes classical interpretations and sharia business literature to develop an integrative theoretical framework. The results show that tawakkal is not only spiritually valuable, but can also strengthen strategy, ethics, and risk management in sharia business. The case studies of Bank Syariah Indonesia (BSI) and 212 Mart show how the value of tawakkal can be internalized in organizational culture and operational decision making. This study recommends that the value of tawakkal be made an important part of entrepreneurship training and sharia business governance.